2018
DOI: 10.1007/978-3-030-04028-4_34
|View full text |Cite
|
Sign up to set email alerts
|

Director’s Cut - Analysis of Aspects of Interactive Storytelling for VR Films

Abstract: To explore methods that are currently used by professional virtual reality (VR) filmmakers to tell their stories and guide users, we analyze how end-users view 360 • video in the presence of directional cues and evaluate if they are able to follow the actual story of narrative 360 • films. In this context, we first collected data from five professional VR filmmakers. The data contains eight 360 • videos, the directors cut, which is the intended viewing direction of the director, plot points and directional cue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 20 publications
4
16
0
1
Order By: Relevance
“…The idea of SD came from previous VR experiments where users would have appreciated more time to get their bearings before too much action unfolds, hence suggesting that temporarily slowing down a scene might help to better immerse into the environment. It is also corroborated by Fearghail et al in [16] who found that longer shots were less disorientating because the user had enough time to explore the environment at their own pace. By lowering the playback speed, a SD gives more time for the playback buffer to fill with high quality video segments, thereby preserving the visual quality and improving the impression of reality.…”
Section: Slow Downsupporting
confidence: 55%
“…The idea of SD came from previous VR experiments where users would have appreciated more time to get their bearings before too much action unfolds, hence suggesting that temporarily slowing down a scene might help to better immerse into the environment. It is also corroborated by Fearghail et al in [16] who found that longer shots were less disorientating because the user had enough time to explore the environment at their own pace. By lowering the playback speed, a SD gives more time for the playback buffer to fill with high quality video segments, thereby preserving the visual quality and improving the impression of reality.…”
Section: Slow Downsupporting
confidence: 55%
“…In order to bridge the gap between traditional and 360°cinematography, Mateer [18] discusses how different existing film directing techniques could be applied in this new emerging field. Focusing on the field of cinematography for 360°content, Knorr et al [12] and Fearghail et al [23] analyze users' behavior while watching 360 • movies by taking into account the intended viewing orientation designed by the director, to verify whether users follow this intended path when watching the film. Fearghail et al [6] use the same dataset to identify the scene elements attracting users' attention.…”
Section: Related Workmentioning
confidence: 99%
“…Focusing on the field of cinematography for 360°content, Knorr et al [12] and Fearghail et al [23] analyze users' behavior while watching 360 • movies by taking into account the intended viewing orientation designed by the director, to verify whether users follow this intended path when watching the film. Fearghail et al [6] use the same dataset to identify the scene elements attracting users' attention. They analyze how cuts affect storytelling and derive some insights about how to redirect users' attention to the main action of the scene, such as using graphical elements and matching the orientation of interesting parts of the story across transitions.…”
Section: Related Workmentioning
confidence: 99%
“…A HMD-based Director's Cut dataset has been proposed in Knorr et al [24] to evaluate the users' attention in storyteller ODV. An interactive storytelling perspective was then presented in [15,16]. More recently, Nasrabadi et al [31] investigated the impact of camera motion on HMD navigation trajectories using the clique-based clustering presented in [44].…”
Section: Studies Related To Odv Dataset and User Behaviour Analysismentioning
confidence: 99%